2022
DOI: 10.1038/s41467-022-28638-5
|View full text |Cite
|
Sign up to set email alerts
|

Rough and smooth variants of Mycobacterium abscessus are differentially controlled by host immunity during chronic infection of adult zebrafish

Abstract: Prevalence of Mycobacterium abscessus infections is increasing in patients with respiratory comorbidities. After initial colonisation, M. abscessus smooth colony (S) variants can undergo an irreversible genetic switch into highly inflammatory, rough colony (R) variants, often associated with a decline in pulmonary function. Here, we use an adult zebrafish model of chronic infection with R and S variants to study M. abscessus pathogenesis in the context of fully functioning host immunity. We show that infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…A recent study using the established zebrafish model of Mabs pathogenesis demonstrated that growth of the inflammatory Mabs rough variant (the morphotype used in our study) results from host TNFa-driven necrotic granulomas. Restriction of virulent Mabs rough variant growth is achieved by host T regulatory cells which associate with these granulomas (43). These results parallel our immunologic findings in which a reduced percentage of T regulatory cells in IFT88 KO mice is associated with increased Mabs growth using a completely different model of Mabs infection.…”
Section: B Asupporting
confidence: 86%
“…A recent study using the established zebrafish model of Mabs pathogenesis demonstrated that growth of the inflammatory Mabs rough variant (the morphotype used in our study) results from host TNFa-driven necrotic granulomas. Restriction of virulent Mabs rough variant growth is achieved by host T regulatory cells which associate with these granulomas (43). These results parallel our immunologic findings in which a reduced percentage of T regulatory cells in IFT88 KO mice is associated with increased Mabs growth using a completely different model of Mabs infection.…”
Section: B Asupporting
confidence: 86%
“…The optical transparency of embryos has been used to visualize the formation of extracellular cords by the R variant in vivo. Using this in vivo model, some authors [ 31 , 32 ] described the ability of both variants to induce granulomas and confirmed the hypervirulence of the R morphotype related to the massive production of extracellular cords. As observed in these studies on the zebrafish infection model, M. abscessus can irreversibly switch from the smooth to the rough variant during persistent infection, resulting in granuloma rupture and bacterial cord formation [ 19 , 31 ].…”
Section: Models Of Intracellular Survivalmentioning
confidence: 82%
“…The entire aerosol procedure takes approximately 1 hour to complete, of which the first 20 minutes are for Mtb aerosolization [ 10 , 14 , 15 , 17 , 26 ]. Mtb forms aggregates in liquid cultures [ 8 , 39 42 ] that are disrupted by adding detergents such as Tween 80 or Tyloxapol in small quantities (0.05–0.1%) [ 10 , 14 , 15 , 26 , 43 ]. Antifoam is added to Mtb cultures that destabilize foam during aerosol procedures.…”
Section: Discussionmentioning
confidence: 99%